Model Pembelajaran Problem Based Learning (PBL) dalam Pembelajaran SKI di MAN 2 Kota Bengkulu - Rina Andriyani Putri; Khoirun Nur Fitri; Ulfa Ningsih; Reyhan Arifqi Khalqi; Titin Sumarni (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the challenges faced by teachers in implementing effective and smooth learning processes, particularly in implementing the Problem Based Learning (PBL) model in Islamic Cultural History (SKI) learning at MAN 2 Bengkulu City. Teachers, as crucial components in the learning process, need to pay attention to students' needs and characteristics in preparing meaningful learning. The PBL model is one of the alternative learning approaches that uses problems as a starting point for students to develop critical thinking skills. This research employed a qualitative approach with research subjects comprising teachers and eleventh-grade students at MAN 2 Bengkulu City. Data collection was conducted through observation, in-depth interviews, and documentation. The research results identified several obstacles in PBL implementation, namely: (1) limited learning time; (2) minimal supporting facilities; (3) variations in student ability levels and characteristics; and (4) lack of interaction and communication between teachers and students. This research also produced strategies to overcome these obstacles, including thorough preparation, effective time management, and development of teachers' abilities to facilitate problem-based learning. These findings contribute to the development of more effective SKI learning practices with a PBL approach in madrasas.